PEMANFAATAN TEKNOLOGI AUGMENTED REALITY UNTUK PENGEMBANGAN BAHAN AJAR MATERI KOMPUTER JARINGAN - Listia Nuraini; Dwi Ratnawati (JPTE FT UNY, 2021)
ABSTRACT:This study aims to develop Augmented Reality based learning media on computer network subject. The research method used in developing educational games is the research and development (RD) method adapted from Borg Gall. The steps of study namely needs analysis, identification of product specifications, product development, product validation, product revision and product testing. The subject of this study was students of class X at Vocational High School. The object of this study was Augmented Reality based learning media on computer network. The test results indicated that this media is feasible to use. The score of product validation gained 73.07% from media experts while it gained 87.5% from material experts under very decent category. Moreover, it gained 85,26% from product users under very feasible category. In addition, the effectiveness test indicated that the result was quite effective with a percentage of 64.41%. Therefore, it could be implied that this learning media was feasible and effective to use in learning process.ABSTRAK:Tujuan penelitian ini adalah pengembangan media pembelajaran berbasis Augmented Reality pada mata pelajaran jaringan komputer. Metode penelitian yang digunakan dalam mengembangkan game edukasi yaitu metode research and development (RD) yang diadaptasi dari Borg Gall dengan beberapa tahapan. Adapun langkahnya adalah analisis kebutuhan, identifikasi spesifikasi produk, pengembangan produk, validasi produk, revisi produk dan uji coba produk. Subjek penelitian ini adalah siswa kelas X SMK. Objek penelitian adalah media pembelajaran jaringan komputer berbasis Augmented Reality. Hasil ujicoba menyatakan bahwa media ini layak digunakan dengan prosentasi dari ahli media sebesar 73,07%, ahli materi mendapat 87,5% dengan kategori sangat layak, sedangkan pengguna mendapatkan 85,26% dengan kategori sangat layak. Sedangkan uji efektivitas menyatakan cukup efektif dengan prosentase 64,41%, sehingga disimpulkan bahwa media pembelajaran ini layak dan efektif digunakan dalam pembelajaran.